If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -7 = 5x + -7 Reorder the terms: -7 + x = 5x + -7 Reorder the terms: -7 + x = -7 + 5x Add '7' to each side of the equation. -7 + 7 + x = -7 + 7 + 5x Combine like terms: -7 + 7 = 0 0 + x = -7 + 7 + 5x x = -7 + 7 + 5x Combine like terms: -7 + 7 = 0 x = 0 + 5x x = 5x Solving x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. x + -5x = 5x + -5x Combine like terms: x + -5x = -4x -4x = 5x + -5x Combine like terms: 5x + -5x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| -6=-6x+6(2x-13) | | (x^2+9)+(6x)=100 | | -24+6v=v-9 | | 3+3n-8n=-7 | | -9=5q/2-1/4(-6q+4) | | 163=4x+3(1-8k) | | 30x=6x-54 | | 5/3+17/6 | | 7a-9=-19+6a | | 110+.40x=30+.80x | | 8v+v=9 | | 4y+2y=48 | | 45y^3z^10/5y^3z | | f(x)=7x^2-4x | | k-1/3(1-9k)=2/3 | | y=2x-1forx | | 22-8m=-8m-11m | | 9+6m=45 | | -4-6n=5-9n | | (m^5n)^-2/m^-2n^3 | | x+3+3x-(6)=180 | | 1.2-0.3m=1.8 | | z(z^2+1)=5+z^3 | | 1=k+8/15 | | 6/7*9/16 | | -7k-k=-10k | | -116=-7x+2(-7x+5) | | 4.8/3 | | -7k-k=10k | | x(6x-6)=(6+8)(x-7) | | 15+3x+1=7x+1 | | 6(-2)-3(-5)/4-2 |